1977
DOI: 10.1002/1097-0142(197708)40:2<680::aid-cncr2820400214>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Viral oncolysate in the management of malignant melanoma. II. Clinical studies

Abstract: Melanoma cell oncolysate, prepared with Newcastle disease virus, was administered as an immunostimulant to 13 patients with metastatic melanoma. The oncolysate was well tolerated. Six treated patients evidenced a decrease in the size of skin nodules or diseased lymph nodes. Visceral lesions were not favorably influenced to any marked degree. One case of fulminating disease showed a change to slow progression and survived a year longer than was otherwise expected. Another patient, whose melanoma could not be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…This risk is not easy to quantify, and it is noteworthy that certain viruses of animal origin (e.g., NDV) have been administered so frequently to humans without adverse consequences that they are now considered to be safe platforms for the development of oncolytics. [70][71][72][73]80,97 Most of the oncolytic viruses currently in clinical testing are attenuated derivatives of prevalent human pathogens. Typically, in recent years, they have been genetically engineered to further attenuate their pathogenicity, increase their oncolytic potency, or enhance their specificity for cancer tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This risk is not easy to quantify, and it is noteworthy that certain viruses of animal origin (e.g., NDV) have been administered so frequently to humans without adverse consequences that they are now considered to be safe platforms for the development of oncolytics. [70][71][72][73]80,97 Most of the oncolytic viruses currently in clinical testing are attenuated derivatives of prevalent human pathogens. Typically, in recent years, they have been genetically engineered to further attenuate their pathogenicity, increase their oncolytic potency, or enhance their specificity for cancer tissue.…”
Section: Discussionmentioning
confidence: 99%
“…71 Newcastle disease virus continues to be used in cancer therapy and has been reported in follow-up studies to provide remissions lasting at least 10 years. 72,73 Whereas much attention had been given to viral adaptation being advantageous for targeting, not much focus had yet been placed on adaptations that a non-human pathogen might acquire that could increase its virulence in a host not normally susceptible. Introduction of wild-type viruses in a traditionally naïve host where populations have not evolved any resistance to the virus would today be considered quite risky.…”
Section: Circumventing Pathogenicity: Using Animal Viruses For Human mentioning
confidence: 99%
“…Viral lysates (called oncolysate) have been used in the past to vaccinate human against cancer (45). Those few trials have shown some degrees of success, but results have been ambiguous (39,46,47). Remarkably, treatment with viral oncolysates showed better overall survival than radio-and chemotherapy, probably because of the harmful effects that these conventional therapies have on the immune system (48).…”
Section: Discussionmentioning
confidence: 99%
“…Subse quently, NDV has been used both as an anti cancer agent in several clinical trials [26]. In the recent years, the reverse genetics technology allowed to generate recombinant strains from non segmented negative strand RNA viruses and allowed to recover recombi nant NDV entirely from cloned cDNA of the non lytic strain LaSota [27].…”
Section: Potential Of Ndv In Cancer Therapymentioning
confidence: 99%